2008
DOI: 10.1111/j.1572-0241.2008.01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin Inhibits Hepatitis C Replication in Humans

Abstract: FLV used as monotherapy in vivo showed suppressive effects of HCV clinically that are modest, variable, and often short-lived. These findings support "proof-of-concept" for pilot trials combining fluvastatin with standard therapy. Statins and fluvastatin, in particular, appear to be safe for use in hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 22 publications
3
141
1
1
Order By: Relevance
“…32 Another surprising effect is its antiviral activity. 33 Simvastatin is active against RNA viruses and acts as monotherapy against chronic hepatitis C virus in humans. It has been shown to act in vitro against hepatitis B virus.…”
Section: Anti-rejection Drugs (Agents That Suppress the Immune System)mentioning
confidence: 99%
“…32 Another surprising effect is its antiviral activity. 33 Simvastatin is active against RNA viruses and acts as monotherapy against chronic hepatitis C virus in humans. It has been shown to act in vitro against hepatitis B virus.…”
Section: Anti-rejection Drugs (Agents That Suppress the Immune System)mentioning
confidence: 99%
“…23 Alternatively, another study using high-dose fluvastatin showed a modest decrease in HCV RNA replication in 50% of patients. 24 Little is known about the relationship between highdensity lipoprotein (HDL) and the virological response to PEG-IFN and RBV. HDL, a scavenger receptor class B type 1 receptor ligand, may modulate the cell entry of the virus via scavenger receptor class B type 1.…”
mentioning
confidence: 99%
“…All reactions were followed by thin layer chromatography (TLC) on kiesel gel F254 precoated plates (Merck). Starting materials sulfonyl and carbonyl hydrazides were synthesized and purified according to literature procedures (Goyal et al, 2016;Brandes, et al, 2005;Bader et al, 2008;Kumaraswamy et al, 2008;Surendiran et al, 2012;xie, et al, 2012). Moreover, the compounds 3 and 4 were commercially available and purchased from Sigma-Aldrich.…”
Section: General Methodsmentioning
confidence: 99%